The Psychological Well-being of Elderly Caregivers at the Elderly Social Welfare Service - Wanu, Fransiskus Kadi; Syamruth, Yendris Krisno; Pello, Shella C. (Journal of Health and Behavioral Science, 2025)
Elderly caregivers are vital in supporting older adults, especially in social institutions, yet face emotional strain, heavy workloads, and limited support. This study explores the psychological well-being of individuals at the UPTD Elderly Social Welfare Service in Kupang, using a descriptive qualitative approach. Data from five caregivers with over one year of experience were gathered through semi-structured interviews and analyzed thematically. Three key themes emerged: acceptance, caregiving challenges, and social support. Caregivers adapted emotionally, faced physical and emotional stress, and coped through spirituality and peer support. Family and institutional support were crucial in building resilience, highlighting the need for targeted support systems in elderly care environments.